The Demoiselle crane (Anthropoides virgo) population genetic structure in Russia - E. A. Mudrik; Е. I. Ilyashenko; О. А. Goroshko; T. A. Kashentseva; М. V. Korepov; I. A. Sikorskiy; G. S. Dzhamirzoev; V. Yu. Ilyashenko; D. V. Politov (Вавиловский журнал генетики и селекции)
The Demoiselle crane (Anthropoides virgo Linneaus, 1758) is a widespread crane species of Eurasia distributed in the steppe and semi-desert zones from southeast Ukraine eastward to Northern China. The Demoiselle crane uses two wintering grounds in Africa and India corresponding to the European and Asian breeding parts of the range subdivided into several spatially separated breeding flocks. The first estimates of the genetic diversity and differentiation have been obtained from five of them: 1) Azov & Black Sea, 2) Caspian, 3) Volga & Ural, 4) South Siberian and 5) Eastern Asian sampled across the total breeding range in Russia using data from 10 microsatellite loci and the 1 003-bp control region of mitochondrial DNA. In total, the Demoiselle crane demonstrates high level of observed (HO = 0.638 ± 0.032) and expected (HE = 0.657 ± 0.023) hete-rozygosity and haplotype diversity (h = 0.960). Genetic differentiation among populations has shown to be weak for both the microsatellite loci (Wright’s FST = 0.052 or AMOVA estimate 0.016) and mtDNA (FST = 0.040). No evidence of significant population structuring of the Demoiselle crane has been found using the STRUCTURE analysis of multilocus microsatellite genotypes and the NETWORK grouping of control region haplotypes. Despite the haplotype diversity was high, the nucleotide diversity of the species was low (0.0033 ± 0.0003). Negative but non-significant Tajima’s and Fu’s tests did not suggest the recent population expansion in the Demoiselle crane evolutionary history which contrasts to other cranes of the Palearctic (the Eurasian crane Grus grus, and the Hooded crane G. monacha). These data indicate more stable conditions for the Demoiselle crane breeding groups in the steppe zone in Pleistocene as compared to boreal and subarctic breeding grounds of other crane species.